2019
DOI: 10.3354/cr01543
|View full text |Cite
|
Sign up to set email alerts
|

East European chironomid-based calibration model for past summer temperature reconstructions

Abstract: Understanding local patterns and large scale processes in past climate necessitates detailed network of temperature reconstructions. In this study, a merged temperature inference model using fossil chironomid (Diptera: Chironomidae) datasets from Finland and Poland was constructed to fill the lack of an applicable training set for East European sites. The developed weighted averaging-partial least squares (WA-PLS) inference model showed favorable performance statistics suggesting that the model can be useful f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 69 publications
(77 reference statements)
1
37
0
Order By: Relevance
“…2015; Luoto et al . 2019). Palaeotemperature data were interpreted using Norwegian, Russian and Swiss models and the recently combined East European model (Luoto et al .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2015; Luoto et al . 2019). Palaeotemperature data were interpreted using Norwegian, Russian and Swiss models and the recently combined East European model (Luoto et al .…”
Section: Discussionmentioning
confidence: 99%
“…Palaeotemperature data were interpreted using Norwegian, Russian and Swiss models and the recently combined East European model (Luoto et al . 2019). The studies showed that even the same local data provide results that are similar to or different from each other and from the hemispheric temperatures reflected by the GISP2 ice‐core record depending on the model applied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations